Extraordinarily strong magneto-responsiveness in phase-separated LaFe2Si. (15th August 2021) - Pathak, Arjun K.; Mudryk, Yaroslav; Zarkevich, Nikolai A.; Ryan, Dominic H.; Johnson, Duane D.; Pecharsky, Vitalij K.
Abstract: Materials responding vigorously to minor variations of external stimuli with negligible hysteresis could revolutionize many of the energy technologies, including refrigeration, actuation, and sensing. We report a combined experimental and theoretical study of a two-phase composite, naturally formed at the LaFe2 Si stoichiometry, which exhibits a nearly anhysteretic, two-step first-order ferromagnetic-to-paramagnetic phase transformation with enhanced sensitivity to an external magnetic field. Other unusual properties include a large plateau-like positive magnetoresistance, magnetic-field-induced temperature and entropy changes occurring over a wide temperature range, and a Griffiths-like phase associated with short-range ferromagnetic clustering in the paramagnetic state. The heat capacity, magnetization, Mössbauer spectroscopy, and electrical resistivity, all exhibit characteristic, unusually sharp, first-order discontinuities even in magnetic fields as high as 100 kOe. We expect that similar phenomena could be designed in other mixed-phase systems, leading to novel functionalities, such as giant caloric effects in many yet undiscovered or/and underperforming intermetallic compounds. Graphical abstract: Image, graphical abstract